ANALYSIS OF DIGITAL MARKETING IMPLEMENTATION IN IMPROVING COMPANY BRANDING AS A BUSINESS ACCELERATOR(CASE STUDY ON PT GAMA INOVASI BERDIKARI) - Azzahra Nimas Allnesyabila; Anas Hidayat (Finance : International Journal of Management Finance, 2024)
This research examines the effectiveness of digital marketing implementation in enhancing the branding of PT Gama Inovasi Berdikari as a business accelerator company. Utilizing a qualitative approach with participatory observation techniques over five months, this study analyzes the company’s digital marketing strategy through interviews, observation, and documentation. The findings indicate that despite significant increases in social media engagement and website traffic, the company’s digital marketing implementation has not been effective in enhancing its specific branding as a business accelerator. While visual branding consistency has been achieved, the diversity of content lacking focus on the business accelerator theme has resulted in the main message not being effectively conveyed to the audience. The research recommends developing more specific and relevant content related to business acceleration, maintaining visual consistency while adding elements that reflect the identity of a business accelerator, and expanding to additional social media platforms relevant to the target audience. These findings contribute to the understanding of the importance of alignment between digital content strategy and specific company branding objectives.